The Effect of the Phonics Method on the Development of English Reading and Speaking Abilities in Children Aged 4–5 Years - Noventy, Elisabeth Susi; Fitri, Ruqoyyah; Setyowati, Sri; Lasarus, Matheos (International Journal of Emerging Research and Review, 2026)
Objective: This study aims to examine the influence of the phonics method on the development of English reading and speaking abilities in children aged 4–5 years at Happy Kids Kindergarten. Method: This study employed a quantitative approach using a quasi-experimental pretest–posttest control group design. The participants consisted of 20 children, divided into a control group (n = 10) and an experimental group (n = 10). Data were collected using a structured observation checklist that measured eight indicators of reading and speaking abilities. The data were analyzed using descriptive statistics and an independent samples t-test. Results: The results showed that the experimental group achieved a mean score of 27.5 (85.9%), which was categorized as “Developing as Expected” (BSH), higher than that of the control group, which obtained a mean score of 20.4 (63.75%) in the category of "Starting to Develop" (MB). The t-test confirmed a significant difference between the two groups (p < 0.05), indicating that the phonics method had a positive effect on children’s English reading and speaking abilities. Novelty: This study contributes to the simultaneous measurement of reading and speaking abilities within a single research design in the context of Indonesian EFL learners aged 4–5 years. Unlike previous studies, which have mostly focused on reading outcomes in L1 or ESL contexts, this study demonstrates that phonics is also effective in improving pronunciation, fluency, vocabulary, and confidence in early EFL learners.